Rationale for aortic annuloplasty to standardise aortic valve repair - Youssefi, Pouya; El-Hamamsy, Ismail; Lansac, Emmanuel (Annals of Cardiothoracic Surgery; Vol 8, No 3 (May 01, 2019): Advanced Techniques in Aortic Valve Repair, 2019)
Available evidence shows that aortic valve repair reduces valve-related mortality and improves quality of life compared to prosthetic aortic valve replacement. One of the most important predictors of bicuspid and tricuspid aortic valve repair failure is the absence of treating a dilated aortic annulus greater than 25–28 mm. Competency of the aortic valve depends on multiple factors including the diameter of the annulus, sinotubular junction, valve cusps and commissures. Dystrophic aortic insufficiency (AI) is the commonest cause of AI in the Western world and is characterised by dilatation of the aortic annulus (≥25 mm), sinuses and/or sinotubular junction (≥30 mm). Depending on whether the sinuses of Valsalva and/or tubular ascending aorta are dilated, three phenotypes can be identified: dilated aortic root, dilated ascending aorta and isolated AI. All three phenotypes are associated with a dilated aortic annulus. Aortic annuloplasty reduces the dilated aortic annulus and improves the surface of coaptation, as in the case of mitral valve repair. In treating AI, it is also important to restore the physiological sinotubular junction/annulus ratio, which can be carried out with remodeling root repair + subvalvular annuloplasty (for dilated aortic root), tubular ascending aorta replacement + subvalvular annuloplasty (for dilated ascending aorta) and double sub- and supra-valvular annuloplasty (for isolated AI). Aortic annuloplasty is now considered an essential component of aortic valve repair and valve-sparing root surgery.